2005
DOI: 10.1179/174329305x23245
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Langmuir–Blodgett nanolayers on microbial adhesion

Abstract: Langmuir-Blodgett (LB) nanolayers of alkyl hydroxamic and phosphonic acids on glass, iron and copper surfaces were studied in the presence of different, corrosion relevant micro-organisms. The quality of monomolecular and multimolecular LB layers was characterised by dynamic contact angle measurement, atomic force microscopy and the sum frequency vibration technique. The inhibition efficiency of microbial adhesion and biofilm formation, which was analysed by the surface visualising technique, epifluorescence m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Although cathodic protection has been reported to effectively inhibit biocorrosion of SS by aerobic bacteria (Guezennec, 1994;Miyanaga et al, 2007), it has been found to have no effect on the adhesion of anaerobic bacteria, and is thus unable to prevent the initiation of pitting corrosion by SRB (de Mele et al, 1995). In view of environmental, ecological, and economical impacts, more recent efforts are focused on developing environmentally benign antimicrobial coatings to prevent bacterial adhesion and biofilm formation (AlDarbi et al, 2002;Sreekumari et al, 2005;Telegdi et al, 2005), as the formation of biofilms is widely recognized as the key step in initiating biocorrosion. Different methods, such as, adsorption, sol-gel processing, and covalent binding, have been used for developing environmentally benign antimicrobial coatings on substrate surfaces to inactivate microorganisms during their initial attachment (Fu et al, 2005;Hu et al, 2005;Lee et al, 2004;Lin et al, 2003;Milović et al, 2005;Tiller et al, 2002;Xu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although cathodic protection has been reported to effectively inhibit biocorrosion of SS by aerobic bacteria (Guezennec, 1994;Miyanaga et al, 2007), it has been found to have no effect on the adhesion of anaerobic bacteria, and is thus unable to prevent the initiation of pitting corrosion by SRB (de Mele et al, 1995). In view of environmental, ecological, and economical impacts, more recent efforts are focused on developing environmentally benign antimicrobial coatings to prevent bacterial adhesion and biofilm formation (AlDarbi et al, 2002;Sreekumari et al, 2005;Telegdi et al, 2005), as the formation of biofilms is widely recognized as the key step in initiating biocorrosion. Different methods, such as, adsorption, sol-gel processing, and covalent binding, have been used for developing environmentally benign antimicrobial coatings on substrate surfaces to inactivate microorganisms during their initial attachment (Fu et al, 2005;Hu et al, 2005;Lee et al, 2004;Lin et al, 2003;Milović et al, 2005;Tiller et al, 2002;Xu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to Folkers and his co-workers [67] alkane hydroxamic acids form more stable SAM overlayers on different metal oxide surfaces than carboxylic acids or phosphonic acid and provide and important thin organic films on copper and silver. The authorsÕ results [68,69] have shown that multimolecular layers of alkane hydroxamic and phosphonic acids (with long carbon chain) on iron surface diminish the corrosion processes and, at the same time, the microbial adhesion. In the present work the influence of temperature and pH values of the subphase on the hydroxamic acid Langmuir monolayer will be shown by surface pressure-area isotherms and by the monolayer morphology visualized by in situ Brewster angle microscope (BAM).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results with carboxylic-, hydroxamic-and phosphonic acids applied in SAM nanocoatings proved the usefulness of these molecular layers as barriers against corrosion and microbial cell adhesion [45][46][47][48][49][50][51]. Recently, the focus of our research moved towards thicker polymer coatings.…”
Section: Introductionmentioning
confidence: 99%